Relativistic Astrophysics and Cosmology A Primer - Hoyng, Peter (Astronomy and Astrophysics Library, 2006)
This book offers a succinct and self-contained treatment of general relativity and its application to neutron stars, black holes, gravitational waves and cosmology, at an intermediate level. The required mathematical concepts are introduced informally, following geometrical intuition as much as possible. The approach is theoretical, but there is ample discussion of observational aspects and instrumental issues where appropriate. Topical issues such as the Gravity Probe B mission, and the physics of interferometer detectors of gravitational waves and the angular power spectrum of the Cosmic Microwave Background are included. The book is written for advanced undergraduates and beginning graduate students in (astro)physics. The reader is assumed to be familiar with linear algebra and analysis, ordinary differential equations, special relativity, and basic thermal physics, but prior knowledge of differential geometry and general relativity is not required. Containing 140 exercises with extensive hints for their solution this book is ideally suited for a lecture course. The author is a senior scientist at the SRON Netherlands Institute for Space Research and teaches regularly at the University of Utrecht.